Postoperative nursing care of patients after breast cancer surgery - Moločko, Anželika; Stundžienė, Rasa (Slauga. Mokslas ir praktika, 2020)
The aim of research work: To find out the postoperative nursing care of patients after breast cancer surgery. Materials and methods. A group of persons under investigation was formed of women who have undergone breast cancer surgery hospitalized in the National Cancer Institute. The following 3 methods were used for the survey: analysis of medical documents, monitoring (a monitoring protocol drawn up by the author) and questionnaire (a survey questionnaire consisting of 17 questions drawn up by the author). On receipt of permission from the National Cancer Institute Director, a monitoring and survey took place in the period November 2016 – February 2017. A total of 60 respondents who have been observed 2 times (in early and late postoperative period) took part in the survey. Data analysis was performed using Microsoft Office Excel 2016 and IBM SPSS Statistics 22 statistical analysis programs. Results. The average age of the respondents was 58.6 ± 11.9 years. The biggest part of the respondents consisted of employed persons (n=34, 56.7 per cent) and persons having a higher/vocational education (n=22, 36.7 per cent). Breastconserving surgery (n=32, 53.3 per cent) has been carried out a little more than breast removal surgery (n=28, 46.7 per cent). Administration of analgesics depended on the pain intensity (p<0.05). Knowledge given to the respondents about purchase of breast prostheses depended on the nature of the surgery (p<0.0005). Conclusions. In the early postoperative period, the main problems of nursing were related to maintaining of safe environment, communicating and sleeping, and in the later postoperative period, they were related to body movement, bowel movements and gender expression in vital activities. In the early postoperative period, respondents were more often provided with assistance in the rehabilitation and maintenance of vital activities, and in the post-operative period, the persons under investigation were provided were trained in terms of prophylaxis and adaptation to the postoperative changes.